ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI PADI DI KECAMATAN PITU RIAWA KABUPATEN SIDRAP - Muhammad Imam Ma'ruf; Citra Ayni Kamaruddin; Arief Muharief (Jurnal Sosial Ekonomi Pertanian, 2019)
Food needs will continue to increase due to year by year, Indonesia's population continues to increase, while the amount of food production cannot compensate for the increase in population. To guarantee national food security, the Indonesian government continues to strive to procure sufficient amounts of rice, including the use of high-yielding seeds, balanced and efficient use of fertilizers, control of pests and diseases, etc. These efforts are only focused on achieving targeted rice production but have not paid attention to the level of income obtained by farmers when cultivating rice compared to cultivating other agricultural commodities. The research was aimed to: (1) determine the income level of a rice farmer, especially in Sidrap District, which is a rice barn area in South Sulawesi Province; and (2) to determine the feasibility of rice farming in the area. One indicator of the feasibility of rice farming can be known based on the value of R / C ratio as well as Break Even Point (BEP) production and Break Even Point (BEP) prices. This study found that the level of income obtained by rice farmers in Pitu Riawa Subdistrict, Sidrap District was Rp. 13,624,672 / ha and was feasible to be cultivated with R / C ratio> 4.24; BEP production of 358 kg; BEP price of IDR 1,152 / kg.